DEMAND CATEGORIZATION DAN INVENTORY MANAGEMENT PRODUK OBAT: STUDI KASUS PADA SUATU TOKO OBAT DI KOTA SOLOK, SUMATERA BARAT - Inna Kholidasari; Lestari Setiawati; Eka Putra (Fakultas Teknik Universitas Tulang Bawang Lampung, 2020)
This research raises the problem of controlling the inventory of medicinal products. The case study was conducted at a drug store in the city of Solok, West Sumatra, where the drug store still has stock out and over stock of various types of drugs it manages. The purpose of this study was to control drug supplies that have a high demand value. Demand data for the period February-April 2020 are grouped with demand value criteria using the Pareto Classification ABC Method. From the demand categorization process, 45 types of drugs were included in A group, which means that this drug group provides a large revenue contribution for the drugstore. Thus, the type A drug group needs more attention from drug store manager in terms of controlling drug supplies. Furthermore, forecasting is carried out for drugs belonging to A drugs group using the Moving Average Method, the Single Exponential Smoothing Method and the Linear Regression Method. The inventory control method adopted is the Economic Order Quantity (EOQ) method. The results showed that the lot size of each type of drug per order ranged from 10-122 units with a safety stock ranging from 5-50 units of product. Then the reorder points obtained ranged from 8-81 units. With the control of drug supplies in place, it is hoped that the stock out and over stock that occurs in drug stores can be minimized.